Pemenuhan Kapasitas Manajemen Pengawasan dan Pengendalian Penyelenggara Infrastruktur Jalan: Studi Kasus Balai Pelaksanaan Jalan Nasional (BPJN) XV Manado - Adriananda Adriananda (Lembaga Administrasi Negara, 2020)
This research was aim to analyzed the increasing management supervision capacity and project control and technical competence of human resources in Ministry of Public Works and Housing in project supervision and control division. Data was collected through interviews of three parties, which are: the supervisor of the activity organizer, the main controller of the activity and the implementing organizational unit. In addition, data was also collected by examining relevant documents at the Ministry of Public Works and Housing. The results of this research indicate that the capacity of the project supervisory and control management and technical competence in managing roads in the Ministry of Public Works and Housing have not yet been fulfilled. To fulfill the project management and supervision management capacity, four main factors are needed: Improving the Quality of the Independent Supervision System in Works Unit (Satker) and The National Road Implementation Agency (BPJN),. The re-organization of The National Road Implementation Agency (BPJN), of the Directorate General of Highways., Improving the quality of Human Resources (HR) Directorate General of Highways, Ministry of Public Works and Housing., To improve the quality of construction service providers (contractors and consultans). This research contributes to the improvement of the project’s supervisory and control management capacity so as to reduce the problematic packages each years, those that are late, unfulfilled quality and pass the fiscal year.Keywords: implementation of national road infrastructure, supervision and control.